2014
DOI: 10.1080/02827581.2014.960894
|View full text |Cite
|
Sign up to set email alerts
|

Look at what they do – a revised approach to communication strategy towards private forest owners

Abstract: Private forest owners in Sweden and other countries are becoming an increasingly heterogeneous group as regards their experience and knowledge of forestry. Over the past decade, a number of studies have been conducted with the aim of describing different aspects of forest owners. However, little attention has been paid to the owners' self-activity and how they learn. With the overall aim of exploring the relationship between self-activity and knowledge to use it as a starting point for new recommendations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Moreover 47% of male forest owners make decisions about forest-related activities by themselves, while only 7% of female owners do so (Mizaraite 2005). The occurrence of self-activity in Swedish family forestry is much more common among male than among female owners (Lidestav and Nordfjell 2005;Häggqvist et al 2014). This is the case in Latvia too, but also the use of service providers for forest management activities are used less often on female-owned estates (Vilkriste 2008).…”
Section: On Gender As a Relational And Structuralizing Categorymentioning
confidence: 95%
“…Moreover 47% of male forest owners make decisions about forest-related activities by themselves, while only 7% of female owners do so (Mizaraite 2005). The occurrence of self-activity in Swedish family forestry is much more common among male than among female owners (Lidestav and Nordfjell 2005;Häggqvist et al 2014). This is the case in Latvia too, but also the use of service providers for forest management activities are used less often on female-owned estates (Vilkriste 2008).…”
Section: On Gender As a Relational And Structuralizing Categorymentioning
confidence: 95%
“…A bulk of PFO studies, including elaborations of forest owner typologies by their management goals, is conducted with support of surveys using traditional statistical (quantitative) techniques, for recent examples see (Häggqvist et al 2014;Lidestav & Lejon 2012). Traditional survey approach is attractive for several reasons (Bliss & Martin 1989) A c c e p t e d M a n u s c r i p t 5 analytical tools are available, and the survey approach enjoys a high degree of acceptance by the scientific community.…”
Section: Excursus On Qualitative Analysismentioning
confidence: 99%
“…Moreover, Fisher and Burton [41] argued that the breakdown in early childhood socialization, due to changes in agricultural practices has led to less interest among children to succeed their parents. Similar risks are apparently possible for private forest owners as the self-activity level is decreasing [37]. Brandth and Overrein [40] also argued that there has been a change in perception of what good parental practices should be (especially for fathers).…”
Section: Discussionmentioning
confidence: 95%
“…Bliss and Martin [35], as well as Lähdesmäki and Matilainen [36], found that working with the forest contributes to the identity of being the owner of the forest. Häggqvist et al [37] found a strong relationship between self-activity and forest knowledge among forest owners. Furthermore, in farming this process of creating a self-identity as a farmer through work has been acknowledged.…”
Section: Discussionmentioning
confidence: 99%